Rare case of congenital anomaly in two different gestational ages: a case series - John, Lopamudra B.; Coumary A, Sendhil; Ghose, Seetesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Acrania is a rare congenital anomaly involving faulty development of membranous flat bones of neurocalvarium. Commonest differential diagnosis is anencephaly. The first case was diagnosed in a second gravida at 13 weeks and terminated by vaginal misoprostol instillation. The second case was diagnosed only by scan at 32 weeks in an unbooked second gravida with previous LSCS. She underwent emergency LSCS for failed induction and a fresh stillborn baby of 1.9 kg was born.